Fertilización convencional y foliar de dos variedades de mani (Arachishypogaea L.) - Castillo Bravo, Jorge Aníbal (2012)
This research was conducted in good faith the canton in 2010, which consisted of conventional fertilization and leaf of two varieties of peanut (Arachishypogaea l.). The overall objective was: To evaluate the conventional fertilization and leaf of two varieties of peanut (Arachishypogaea L.). We used a statistical design of randomized complete blocks with a factorial arrangement modified (2 x 2) + 1. The factors were two varieties of peanuts; INIAP 311 and 308, and types of fertilization, conventional (40 kg / ha of triple superphosphate and muriate of potash) and leaf (2L/ha). The trial lasted 120 days. According to the results, the highest germination n caught the highest percentage of germination reached him for the INIAP factor A 311 with 88.4% for treatments, the 2 (311 + INIAP conventional fertilization) and Witness with 87.6 and 85.6% respectively. The largest crop cycle was obtained by the INIAP 311 with 120 days for the treatments 2 (311 + INIAP conventional fertilization) and the Witness with 120 and 122 days. The earlier the INIAP reached 308 and the treatments 3 (INIAP 308 + organic fertilization) and 4 (conventional fertilization INIAP 308 +) with 117 days each in the crop cycle and 27 days to flowering in all the cases mentioned. The tallest plants at harvest in the factor A caught the INIAP 311 with 51.4 cm, plus treatments 1 (311 + INIAP Organic fertilization) and 2 (311 + INIAP conventional fertilization) with 49.4 and 53, 4 cm correspondingly. The greatest number of pods per plant obtained for the factor A Variety INIAP 308 with 27.8 for the factor B, the conventional fertilization with 27.8 and treatments, the 2 (311 + INIAP conventional fertilization), 3 ( Organic fertilization INIAP 308 +), 4 (308 + INIAP conventional fertilization) and the Witness with 27.5, 27.7, 28.0 and 28.9 respectively. The overall average of seeds per pod found in this study was 3. The weight of 100 seeds the INIAP 308 (Factor A) with an average of 66.1 grams was higher. In factor B, the conventional fertilization showed the highest weight of 100 seeds with an average of 62.4 grams. Treatments 3 (INIAP 308 + organic fertilization) and 4 (308 + INIAP conventional fertilization) obtained the highest weights of 100 seeds with 65.5 and 66.7 g correspondingly. The INIAP 308 had the highest yield per hectare with 4346.5. The conventional fertilization also produced the highest yield per hectare with an average of 3892.9 kilos / ha. Treatments 3 (INIAP 308 + organic fertilization) and 4 (308 + INIAP conventional fertilization) were those who reported the highest yield per hectare at 4312.5 and 4380.5 kilos respectively. In the economic analysis determined that the treatments reported higher profitability were 4 (conventional fertilization INIAP 308 +) and 3 (308 + INIAP Organic fertilization) with values of 2500, 40 and 2417, 30; and a cost benefit 1.7 correspondingly. Finally we concluded the following: Sow commercially INIAP 308 combined with conventional or organic fertilization.